Enhancement of Fracture Toughness Characteristics of Woven Jute Fabric Mat Reinforced Epoxy Composites with SiC Fillers. Issue 1 (31st December 2023) - Arul, M.; Sasikumar, K.S.K.; Sambathkumar, M.; Dineshkumar, Karuppanasamy
ABSTRACT: Natural fiber reinforced composites are attracting the attention of industries toward a sustainable and environment-friendly material for the future demands. The main drawback pertaining to the use of natural fiber composites lies in its inferior strength in comparison to its counterpart synthetic fibers. This research focuses on improving the fracture toughness of woven jute fabric mat with different orientations (0°, 30° and 45°) in epoxy resin by incorporating fillers and tested in universal tensile testing machine. Silicon carbide (SiC) particles of three sizes 26 µm, 54 µm and 72 µm were incorporated in the matrix in different weight ratios (5%, 10% and 15%). The fracture toughness of the jute/epoxy composites increases with the increase in the amount of SiC particles up to 10% addition and then it shows decreasing trend with further addition. The fracture toughness values show upward trend when the fiber orientation changed from 0° to 45°. Fractography of the tested specimen captured by scanning electron microscope which reveals the fracture of fibers and micro cracks in the epoxy matrix due to the applied load. Analysis of variance (ANOVA) is also conducted for predicting the most influencing parameters on the fracture toughness.